Analysis of the Geometry of The Cutting Wedge of the Designed Cutter Based on the Model Obtained by Solving the Inverse Problem of Profiling - Urinov Nodir Nasilloevich (Scientific Trends, 2023)
To assess the performance of the cutter, the nature of the change in the front and rear angles in the end section and in the section, which is the straightening plane of the cylinder, the axis of which coincides with the axis of the cutter, and the radius is equal to the distance from the considered point of the cutting edge to the axis, is considered. It has been established that the error will increase with an increase in the projected diameter of the cutter, the length of the front surface in the normal section, the rake angle and the increase in the angle of inclination of the cutting edge.
Keywords: Radius end mill, durability, tool, cutting edge shape, error, real profile, relief angle, cutting wedge.